2009
DOI: 10.1016/j.jasms.2009.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Surface assisted laser desorption/ionization on two-layered amorphous silicon coated hybrid nanostructures

Abstract: Matrix-free laser desorption/ionization was studied on two-layered sample plates consisting of a substrate and a thin film coating. The effect of the substrate material was studied by depositing thin films of amorphous silicon on top of silicon, silica, polymeric photoresist SU-8, and an inorganic-organic hybrid. Des-arg 9 -bradykinin signal intensity was used to evaluate the sample plates. Silica and hybrid substrates were found to give superior signals compared with silicon and SU-8 because of thermal insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…These results agree well with previous reports of highly hydrophilic oxygen plasma treated PS surfaces. The initial contact angles of nitrogen plasma treated surfaces were around 10 and after 100 days the contact angles of dry stored and rewashed samples had recovered to around 42 and 60 , respectively. Overall, PS was the material which kept its hydrophilicity for the longest time, although most of the samples seem to still be ongoing slow hydrophobic recovery after 100 days.…”
Section: F Psmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree well with previous reports of highly hydrophilic oxygen plasma treated PS surfaces. The initial contact angles of nitrogen plasma treated surfaces were around 10 and after 100 days the contact angles of dry stored and rewashed samples had recovered to around 42 and 60 , respectively. Overall, PS was the material which kept its hydrophilicity for the longest time, although most of the samples seem to still be ongoing slow hydrophobic recovery after 100 days.…”
Section: F Psmentioning
confidence: 99%
“…40 Applications of ORMOCERs include abrasion resistant transparent coatings, 40 barrier layers for food packaging, 40 elements for optical applications, 40 microchip capillary electrophoresis, 15,41 and surface assisted laser desorption ionization mass spectrometry. 42 We have recently studied the hydrophilization and pore formation process of ORMOCOMP by an oxygen plasma process using a different oxygen plasma process (reactive ion etching). 43 In that study, we found that the contact angles of all but the most clearly porous samples recovered to around 45 in three weeks, while the strongly porous samples retained complete wetting during that period.…”
Section: H Ormocompmentioning
confidence: 99%
“…17) Metal-oxide-based semiconductors with good UV absorbance are also promising candidates for matrix-free LDI-MS applications, such as titania sol-gel films, 18) titania nanotube arrays, 19) zinc oxide nanowires, 20) mesoporous tungsten titanium oxides, 21) and germanium nanodots. 22) In addition, double-or multilayer-coated hybrid substrates such as metal-coated porous alumina (platinum/alumina), 23), 24) two-layered amorphous silicon, 25) titaniaprinted aluminum foils (titania/aluminum), 26) silverparticle-deposited porous silicon (silver/silicon), 27) gold nanorods on porous alumina (gold/alumina), 28) layerby-layer (LBL) self-assembled films (polymer/gold), 29) Pt nanoflowers on a scratched silicon, 30) DVDs coated with diamond-like carbon, 31) and cationic-polymercoated graphite sheets (polymer/graphite) 32) are considered to be promising materials for matrix-free LDI-MS because the layer properties of these substances can be varied independently. Further, these hybridization e#ects can improve the e$ciency of matrix-free LDI-MS.…”
Section: )῍9)mentioning
confidence: 99%
“…Double-or multilayer-coated hybrid substrates, such as metal-coated porous alumina (platinum/alumina), 41,44 two-layered amorphous silicon, 64 titania-printed aluminum foils (titania/aluminum), 65 layer-by-layer (LBL) self-assembled films, 66,67 and DVDs coated with diamond-like carbon 68 are considered to be promising materials for SALDI-MS because the layer properties of these substances can be varied using diffrernt layer combinations.…”
Section: ·5 Multilayer-coated Substratesmentioning
confidence: 99%
“…64 With regard to the coating layer, an amorphous silicon coating was superior to other coatings because of its UV absorptivity and favorable surface chemistry. Good signals were obtained from the combination of a titania substrate with an amorphous silicon coating, but not from alumina-coated, silicon-nitride-coated, or uncoated sample plates.…”
Section: ·5 Multilayer-coated Substratesmentioning
confidence: 99%